New or rare Madagascar tiger beetles—27. Pogonostoma (Pogonostoma) andasibense sp. nov., and a revised key to the Pogonostoma (P.) elegans species-group (Coleoptera: Cicindelidae) - Moravec, Jiří; Wiesner, Jürgen (Zootaxa, 2026)
A new species of the genus Pogonostoma Klug, 1835, P. (Pogonostoma) andasibense sp. nov. is described from Analamazaotra (= Andasibe-Mantadia) National Park in eastern Madagascar. This new species is placed here into the Pogonostoma (s. str.) elegans species-group, established by Rivalier (1970) as modified by Moravec (2007) and here. A revised key to species of the species-group is presented in order to supplement the key by Moravec (2007) and Moravec & Vybíral (2020). The new species is compared to other similar taxa with references to the illustrations of their type and other specimens in the monograph by Moravec (2007). Habitus and diagnostic characters of the new species are illustrated in colour photographs. The history of the protected area of the type locality is discussed according to the recent status of the Analamazaotra National Park. A map of distribution of the new species and a map showing protected areas of Madagascar are also presented.